Iron ore waste rock unfired water permeable brick and preparation method thereof

By adding appropriate amounts of tailings, silicate cement and other raw materials to iron ore waste stone, and using press molding method to prepare burn-free permeable bricks, the problem of iron ore waste stone utilization is solved, efficient and environmentally friendly building materials preparation is achieved, and the mechanical strength and water permeability of the materials are improved.

CN119613043APending Publication Date: 2025-03-14SHANGLUO UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411766473.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize iron ore waste, fail to fully utilize its useful mineral components, and lacks environmentally friendly and efficient ways to utilize building materials.

Method used

The raw materials such as iron ore waste stone, tailings, silicate cement, water reducing agent, pore-making agent and water are prepared by press molding, and the raw material formula and process are optimized to improve the mechanical strength and water permeability of the material.

Benefits of technology

It has achieved efficient utilization of iron ore waste stone, and prepared burn-free permeable bricks with high mechanical strength and good water permeability, solved resource and environmental problems, and provided reliable technical support for urban planning and construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169073220000081
    Figure BDA0005169073220000081
  • Figure BDA0005169073220000091
    Figure BDA0005169073220000091
Patent Text Reader

Abstract

The invention discloses an iron ore waste rock unfired water permeable brick and a preparation method thereof. The water permeable brick is prepared from the following raw materials in parts by weight: 30-80 parts of iron ore waste rock, 10-30 parts of tailings, 10-30 parts of cement, 1-3 parts of a water reducing agent, 3-6 parts of a pore forming agent and 5-15 parts of water. The baking-free high-performance water permeable brick is prepared by adopting iron ore waste rock as aggregate, adding a proper amount of Portland cement and tailings and adopting a compression molding method. By optimizing the raw material formula and the preparation process, the mechanical strength and the water permeability of the water permeable brick are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building material preparation, and particularly relates to an iron ore waste rock unfired permeable brick and a preparation method thereof. Background Art

[0002] Iron ore waste rock mainly comes from stripping, blasting and other operations during iron ore mining and beneficiation. These waste rocks usually contain a certain proportion of useful mineral components, such as iron and other metal or non-metal components. The treatment and utilization of iron ore waste rock is an important issue faced by mining companies and a key area of ​​environmental protection and comprehensive resource utilization.

[0003] At present, my country's treatment methods for iron ore waste rock mainly include the following: backfilling of goaf, using waste rock directly to backfill goaf, which not only reduces land occupation but also stabilizes the surface structure; engineering application, waste rock can be used as road construction material or other construction materials, thereby reducing waste emissions and improving resource utilization; recycling iron ore, through dry magnetic separation equipment and other technical means, a small amount of valuable iron ore resources are recovered from waste rock; preparation of sand and gravel aggregate, processing waste rock into construction sand and gravel aggregates of different particle sizes (such as machine-made sand, stone powder, etc.), and using dry magnetic separation equipment to recover the iron ore resources therein.

[0004] Studying how to utilize iron ore waste rock and convert it into building materials can help reduce the impact of waste resources on the environment and improve resource utilization efficiency. As a new type of green and environmentally friendly building material, permeable bricks can solve the problem of hardening of urban surfaces, create a high-quality natural living environment, and maintain the ecological balance of the city. Therefore, studying the preparation of unfired permeable bricks from iron ore waste rock can help solve resource problems and provide reliable technical support for urban planning and construction. Summary of the invention

[0005] The object of the present invention is to provide an iron ore waste rock unfired permeable brick and a preparation method thereof.

[0006] An iron ore waste rock unfired permeable brick is made of the following raw materials in parts by weight: 30-80 parts of iron ore waste rock, 10-30 parts of tailings, 10-30 parts of cement, 1-3 parts of water reducing agent, 3-6 parts of pore-forming agent and 5-15 parts of water.

[0007] The tailings are one or more of iron tailings, nickel tailings, copper tailings, zinc tailings, molybdenum tailings and tin tailings.

[0008] Preferably, the tailings are mixed tailings of iron tailings and tin tailings in a mass ratio of 2:1.

[0009] The cement is P.O52.5 ordinary Portland cement.

[0010] The water reducing agent is one or more of calcium lignin sulfonate, sodium lignin sulfonate, and sodium β-naphthalene sulfonate formaldehyde condensate.

[0011] The particle size of the iron ore waste rock is 5-12 mm.

[0012] The pore-forming agent is a mixture of activated carbon and calcined zeolite powder in a mass ratio of 1:1.

[0013] The method for preparing the iron ore waste rock unfired permeable brick is carried out according to the following steps:

[0014] (1) According to the weight ratio, 30-80 parts of iron ore waste rock are put into a 5-12 mm square sieve for screening, the screened iron ore waste rock is put into a container for cleaning and drying, 10-30 parts of tailings, 10-30 parts of cement, 1-3 parts of water reducer, 3-6 parts of pore former, and 5-15 parts of water are added, and after mixing evenly, the mixture is put into a cement mortar mixer and stirred for 3-6 minutes to prepare a slurry;

[0015] (2) placing the stirred slurry into a mold, applying pressure and maintaining the pressure for 30-80 seconds to press it into a green body;

[0016] (3) The green body is naturally dried and then cured.

[0017] The applied pressure in step (2) is 4-12 MPa.

[0018] The curing temperature in step (3) is 20-30° C., the curing humidity is greater than 95%, and the curing time is 20-35 days.

[0019] Beneficial effects of the present invention: The present invention uses iron ore waste as aggregate, adds an appropriate amount of silicate cement and tailings, and adopts a pressing molding method to prepare non-fired high-performance permeable bricks. By optimizing the raw material formula and the preparation process, the mechanical strength and water permeability of the permeable bricks are improved. The combination of iron tailings and tin tailings in the formula improves the mechanical properties of the material, and the combination of activated carbon and calcined zeolite powder improves the water permeability of the material. DETAILED DESCRIPTION

[0020] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0021] Example 1

[0022] An iron ore waste rock unfired permeable brick is made of the following raw materials in parts by weight: 50 parts of iron ore waste rock, 20 parts of tailings, 20 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 5 parts of pore-forming agent, and 10 parts of water; the tailings are mixed tailings of iron tailings and tin tailings in a mass ratio of 2:1; the pore-forming agent is a mixture of activated carbon and calcined zeolite powder in a mass ratio of 1:1; the particle size of the iron ore waste rock is 8 mm.

[0023] The method for preparing the iron ore waste rock unfired permeable brick is carried out according to the following steps:

[0024] (1) According to the weight ratio, 50 parts of iron ore waste rock were put into an 8 mm square sieve for screening, the screened iron ore waste rock was put into a container for cleaning and drying, 20 parts of tailings, 20 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 5 parts of pore formers, and 10 parts of water were added, and the mixture was evenly mixed and then put into a cement mortar mixer for stirring for 5 minutes to prepare a slurry;

[0025] (2) placing the stirred slurry into a mold, applying a pressure of 8 MPa and maintaining the pressure for 50 seconds to press it into a green body;

[0026] (3) The green body is naturally dried and then cured; the curing temperature is 25° C., the curing humidity is 96%, and the curing time is 28 days.

[0027] Example 2

[0028] An iron ore waste rock unfired permeable brick is made of the following raw materials in parts by weight: 35 parts of iron ore waste rock, 12 parts of tailings, 12 parts of P.O52.5 ordinary Portland cement, 1 part of sodium lignin sulfonate, 3 parts of pore-forming agent, and 5 parts of water; the tailings are mixed tailings of iron tailings and tin tailings in a mass ratio of 2:1; the pore-forming agent is a mixture of activated carbon and calcined zeolite powder in a mass ratio of 1:1; the particle size of the iron ore waste rock is 6 mm.

[0029] The method for preparing the iron ore waste rock unfired permeable brick is carried out according to the following steps:

[0030] (1) According to the weight ratio, 35 parts of iron ore waste rock were put into a 6 mm square sieve for screening, the screened iron ore waste rock was put into a container for cleaning and drying, 12 parts of tailings, 12 parts of P.O52.5 ordinary Portland cement, 1 part of sodium lignin sulfonate, 5 parts of pore-forming agent, and 5 parts of water were added, and the mixture was evenly mixed and then put into a cement mortar mixer for stirring for 4 minutes to prepare a slurry;

[0031] (2) placing the stirred slurry into a mold, applying a pressure of 6 MPa and maintaining the pressure for 40 seconds to press it into a green body;

[0032] (3) The green body is naturally dried and then cured; the curing temperature is 20° C., the curing humidity is 98%, and the curing time is 34 days.

[0033] Example 3

[0034] An iron ore waste rock unfired permeable brick is made of the following raw materials in parts by weight: 70 parts of iron ore waste rock, 30 parts of tailings, 30 parts of P.O52.5 ordinary Portland cement, 3 parts of sodium β-naphthalenesulfonate formaldehyde condensate, 6 parts of pore-forming agent, and 15 parts of water; the tailings are mixed tailings of iron tailings and tin tailings in a mass ratio of 2:1; the pore-forming agent is a mixture of activated carbon and calcined zeolite powder in a mass ratio of 1:1; the particle size of the iron ore waste rock is 10 mm.

[0035] The method for preparing the iron ore waste rock unfired permeable brick is carried out according to the following steps:

[0036] (1) According to the weight ratio, 70 parts of iron ore waste rock were put into a 10 mm square sieve for screening, the screened iron ore waste rock was put into a container for cleaning and drying, 30 parts of tailings, 30 parts of P.O52.5 ordinary Portland cement, 3 parts of β-naphthalenesulfonate sodium formaldehyde condensate, 6 parts of pore formers, and 15 parts of water were added, and the mixture was evenly mixed and then put into a cement mortar mixer for stirring for 6 minutes to prepare a slurry;

[0037] (2) placing the stirred slurry into a mold, applying a pressure of 10 MPa and maintaining the pressure for 60 seconds to press it into a green body;

[0038] (3) The green body is naturally dried and then cured; the curing temperature is 30° C., the curing humidity is 97%, and the curing time is 22 days.

[0039] Comparative Example 1

[0040] An iron ore waste rock unfired permeable brick is made of the following raw materials in parts by weight: 50 parts of iron ore waste rock, 20 parts of iron tailings, 20 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 5 parts of pore-forming agent, and 10 parts of water; the pore-forming agent is a mixture of activated carbon and calcined zeolite powder in a mass ratio of 1:1; the particle size of the iron ore waste rock is 8 mm.

[0041] The method for preparing the iron ore waste rock unfired permeable brick is carried out according to the following steps:

[0042] (1) According to the weight ratio, 50 parts of iron ore waste rock were put into an 8 mm square sieve for screening, the screened iron ore waste rock was put into a container for cleaning and drying, 20 parts of iron tailings, 20 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 5 parts of pore formers, and 10 parts of water were added, and the mixture was evenly mixed and then put into a cement mortar mixer for stirring for 5 minutes to prepare a slurry;

[0043] (2) placing the stirred slurry into a mold, applying a pressure of 8 MPa and maintaining the pressure for 50 seconds to press it into a green body;

[0044] (3) The green body is naturally dried and then cured; the curing temperature is 25° C., the curing humidity is 96%, and the curing time is 28 days.

[0045] Comparative Example 2

[0046] An iron ore waste rock unfired permeable brick is made of the following raw materials in parts by weight: 50 parts of iron ore waste rock, 20 parts of tin tailings, 20 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 5 parts of pore-forming agent, and 10 parts of water; the pore-forming agent is a mixture of activated carbon and calcined zeolite powder in a mass ratio of 1:1; the particle size of the iron ore waste rock is 8 mm.

[0047] The method for preparing the iron ore waste rock unfired permeable brick is carried out according to the following steps:

[0048] (1) According to the weight ratio, 50 parts of iron ore waste rock were put into an 8 mm square sieve for screening, the screened iron ore waste rock was put into a container for cleaning and drying, 20 parts of tin tailings, 20 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 5 parts of pore formers, and 10 parts of water were added, and the mixture was evenly mixed and then put into a cement mortar mixer for stirring for 5 minutes to prepare a slurry;

[0049] (2) placing the stirred slurry into a mold, applying a pressure of 8 MPa and maintaining the pressure for 50 seconds to press it into a green body;

[0050] (3) The green body is naturally dried and then cured; the curing temperature is 25° C., the curing humidity is 96%, and the curing time is 28 days.

[0051] Comparative Example 3

[0052] An iron ore waste rock unfired permeable brick is made of the following raw materials in parts by weight: 50 parts of iron ore waste rock, 20 parts of tailings, 20 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 5 parts of activated carbon, and 10 parts of water; the tailings are mixed tailings of iron tailings and tin tailings mixed in a mass ratio of 2:1; the particle size of the iron ore waste rock is 8 mm.

[0053] The method for preparing the iron ore waste rock unfired permeable brick is carried out according to the following steps:

[0054] (1) According to the weight ratio, 50 parts of iron ore waste rock were put into an 8 mm square sieve for screening, the screened iron ore waste rock was put into a container for cleaning and drying, 20 parts of tailings, 20 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 5 parts of activated carbon, and 10 parts of water were added, and the mixture was evenly mixed and then put into a cement mortar mixer for stirring for 5 minutes to prepare a slurry;

[0055] (2) placing the stirred slurry into a mold, applying a pressure of 8 MPa and maintaining the pressure for 50 seconds to press it into a green body;

[0056] (3) The green body is naturally dried and then cured; the curing temperature is 25° C., the curing humidity is 96%, and the curing time is 28 days.

[0057] Comparative Example 4

[0058] An iron ore waste rock unfired permeable brick is made of the following raw materials in parts by weight: 50 parts of iron ore waste rock, 20 parts of tailings, 20 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 5 parts of calcined zeolite powder, and 10 parts of water; the tailings are mixed tailings of iron tailings and tin tailings mixed in a mass ratio of 2:1; the particle size of the iron ore waste rock is 8 mm.

[0059] The method for preparing the iron ore waste rock unfired permeable brick is carried out according to the following steps:

[0060] (1) According to the weight ratio, 50 parts of iron ore waste rock were put into an 8 mm square sieve for screening, the screened iron ore waste rock was put into a container for cleaning and drying, 20 parts of tailings, 20 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 5 parts of calcined zeolite powder, and 10 parts of water were added, and the mixture was evenly mixed and then put into a cement mortar mixer for stirring for 5 minutes to prepare a slurry;

[0061] (2) placing the stirred slurry into a mold, applying a pressure of 8 MPa and maintaining the pressure for 50 seconds to press it into a green body;

[0062] (3) The green body is naturally dried and then cured; the curing temperature is 25° C., the curing humidity is 96%, and the curing time is 28 days.

[0063] Experimental example:

[0064] The compressive strength of the samples was tested using a YAW-3000 microcomputer-controlled electro-hydraulic servo pressure testing machine; each material was tested 5 times. SPSS24.0 software was used for statistical analysis, and the quantitative data results were used for ±s (mean ± standard deviation), the Kolmogorov-Smirnov test was used for data normality test, and for data that met the normal distribution, the t test was used to compare the mean differences between the two groups, with P < 0.05 as the difference being statistically significant. The results are shown in Table 1:

[0065] Table 1

[0066]

[0067] Note: * represents P < 0.05 compared with the group in Example 1.

[0068] The water permeability coefficient of the samples was measured according to GB / T 25993-2010 "Permeable Pavement Bricks and Permeable Road Panels" standard, and each material was measured three times; the results are shown in Table 2:

[0069] Table 2

[0070]

[0071] Note: * represents P < 0.05 compared with the group in Example 1.

[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An iron ore waste rock unfired permeable brick, characterized in that: The invention is prepared from the following raw materials in parts by weight: 30-80 parts of iron ore waste, 10-30 parts of tailings, 10-30 parts of cement, 1-3 parts of water reducing agent, 3-6 parts of pore-forming agent and 5-15 parts of water.

2. The iron ore waste rock unfired permeable brick according to claim 1 is characterized in that: The tailings are one or more of iron tailings, nickel tailings, copper tailings, zinc tailings, molybdenum tailings and tin tailings.

3. The iron ore waste rock unfired permeable brick according to claim 2 is characterized in that: The tailings are mixed tailings of iron tailings and tin tailings in a mass ratio of 2:

1.

4. The iron ore waste rock unfired permeable brick according to claim 1, characterized in that: The cement is P.O52.5 ordinary Portland cement.

5. The iron ore waste rock unfired permeable brick according to claim 1, characterized in that: The water reducing agent is one or more of calcium lignin sulfonate, sodium lignin sulfonate, and sodium β-naphthalenesulfonate formaldehyde condensate.

6. The iron ore waste rock unfired permeable brick according to claim 1, characterized in that: The particle size of the iron ore waste rock is 5-12 mm.

7. The iron ore waste rock unfired permeable brick according to claim 1, characterized in that: The pore-forming agent is a mixture of activated carbon and calcined zeolite powder in a mass ratio of 1:

1.

8. The method for preparing the iron ore waste rock unfired permeable brick according to claim 1, characterized in that: Follow these steps: (1) According to the weight ratio, 30-80 parts of iron ore waste rock are put into a 5-12 mm square sieve for screening, the screened iron ore waste rock is put into a container for cleaning and drying, 10-30 parts of tailings, 10-30 parts of cement, 1-3 parts of water reducer, 3-6 parts of pore former, and 5-15 parts of water are added, and after mixing evenly, the mixture is put into a cement mortar mixer and stirred for 3-6 minutes to prepare a slurry; (2) placing the stirred slurry into a mold, applying pressure and maintaining the pressure for 30-80 seconds to press it into a green body; (3) The green body is naturally dried and then cured.

9. The method for preparing the iron ore waste rock unfired permeable brick according to claim 8, characterized in that: The applied pressure in step (2) is 4-12 MPa.

10. The method for preparing the iron ore waste rock unfired permeable brick according to claim 8, characterized in that: The curing temperature in step (3) is 20-30° C., the curing humidity is greater than 95%, and the curing time is 20-35 days.

Citation Information

Cited By

  • Baking-free refractory brick and preparation method thereof

    CN120622940A